Long term impacts of compensatory preschool on health and behavior: Evidence from head start - Pedro Carneiro; Rita Ginja (Uppsala University, Department of Economics, 2012)
This paper provides new estimates of the medium and long-term impacts of Head Start on the health and behavioral problems of its participants. We identify these impacts using discontinuities in the probability of participation induced by program eligibility rules. Our strategy allows us to identify the effect of Head Start for the set of individuals in the neighborhoods of multiple discontinuities, which vary with family size, state and year (as opposed to a smaller set of individuals neighboring a single discontinuity). Participation in the program reduces the incidence of behavioral problems, serious health problems and obesity of male children at ages 12 and 13. It also lowers depression and obesity among adolescents, and reduces engagement in criminal activities for young adults.
urn:nbn:se:uu:diva-168531
Keywords: C21; I28; I38; 330; regression discontinuity design; early childhood development; non-cognitive skills; Head Start; Bildungsfinanzierung; Kinderbetreuung; Wirkungsanalyse; Verhalten; Gesundheit; Regression; USA